Informal organizations and their relationship to decision-making "Field study on a sample of workers of the General Establishment of Tobacco in Lattakia " - Zreka, Yossra; Mohammad, Sahar (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
The aim of this study is to identify informal organizations as an integral part of the organizational structure of institutions and their role in the decision –making process within the institution . To achieve the objectives of the research ,a questionnaire was designed and applied to a sample of the workers of the Tobacco Establishment in Lattakia . The results of the study showed that there is a statistically significant relationship between the involvement of the informal organization in decision-making and the increase in productivity at a level of significance a=0,01 . The study also showed that there is a statistically significant relationship between the involvement of informal organization in decision-making and the efficiency of management in decision-making at a meaningful level a=0,01 . .